Qualidade, compostos bioativos e capacidade antioxidante total de frutos de híbridos comerciais de meloeiro cultivados no CE e RN - Barreto, Norma Danielle Silva (2011)
There is a growing interest about the relation between nutrition and health, with emphasis on the consumption of antioxidants naturally existent in food. In this context, the goal of this study was to evaluate the quality, the bioactive compounds and the total antioxidant capacity in fruits of the main hybrid melons (Yellow, Galia, Pele de Sapo, Charentais, Cantaloupe and Honeydew) produced in RN and CE states in view of adding value through their nutritional and functional properties. The fruits used in the experiment were acquired during the 2009/2010 harvest from commercial farms located in the cities of Icapuí and Quixere in CE state, also Mossoró and Baraunas in RN state. They were sent to the Post Harvest Laboratory of Embrapa in Fortaleza-CE. They were analyzed regarding to average weight, color, longitudinal and transverse diameters, longitudinal and transverse internal cavities, shell thicknesses and flesh, size relation, flesh firmness, pH, titratable acidity, soluble solids, SS/TA, total soluble sugars and reducing, vitamin C, total carotenoids, yellow flavonoids and chlorophyll. For the analyzes of total polyphenols and antioxidant capacity, the fruits were sent to the Bioflavors Laboratory of the FEA/UNICAMP. For physical assessments, fifteen fruits were used for each cultivar analyzed with individual measurements and for chemical assessments were used fifteen fruits, which were divided into three portions (repetitions). The results were submitted to descriptive statistical analysis. All hybrids have titratable acidity, SS/TA ratio, pH and size relation satisfactory for marketing with an emphasis on ' 9150' Yellow; 'PX 4048' Cantaloupe; 'Magisto' Charentais; 'Solarnet' Galia and 'Sancho' Pele de Sapo that had lower transverse internal cavity. Climatic conditions in the border region between RN and CE enable the melon production with soluble solids levels above of the minimum required by the international market and with total polyphenols and total antioxidant capacity levels higher than the reported in international literature. The Cantaloupe and Charentais melons show characteristics satisfactory for vitamin C, total carotenoids, yellow flavonoids, total polyphenols and antioxidant capacity, with emphasis on the hybrids 'PX 4048 ', 'Magritte', 'Magisto', 'Sedina' and 'Caribbean Gold' that had the highest amount of vitamin C and antioxidant capacity, and they can be used to promote the human health